O labirinto da leitura: entre o autor e o leitor em O ano da morte de Ricardo Reis , de José Saramago - Martins, Sara Grünhagen (2016)
This work proposes an analysis of the novel The year of the death of Ricardo Reis, by Portuguese writer José Saramago, which builds the story from a heteronym by Fernando Pes-soa, from other texts and characters of literature and from historical events and figures. First published in 1984, the novel uses the biographical data of Pessoa s heteronyms, making Ri-cardo Reis return to Portugal at the end of 1935, shortly after the death of his creator Fernan-do Pessoa. At first, the heteronym appears with the profile and the characteristics by which he is known: a cold and stand-offish man that seeks to alienate himself from the world as much as possible, a monarchist doctor and poet in his spare time, whose style stands out for its eru-dite language, for the use of odes and for recurring themes and figures, like the gods, death, time and the transience of life. Ricardo Reis is thus a representation of the classic tradition, and as such he is challenged and deconstructed throughout the novel, which confronts him with his view that Wise is he who is satisfied with the spectacle of the world . For the analy-sis of Ricardo Reis transformation in the book, we initially propose a discussion regarding the authorship, inasmuch as, contrary to Saramago s defense of the author at various times, the novel is also a demystification of the author, especially in the confrontation with Pessoa s heteronym. Addressing Saramago s opinions on this regard and aiming to show the way by which his vision is related to a modern revival of the author as the main unit of the text, with consequences to reading, we turn then to the reader s figure as the key point to reflect on the necessary opening of the text, which is what allows the reading and the very construction of a novel such as The year. Therefore, giving more emphasis on a Saramago reader-author, we propose then the analysis of the novel, focusing on Ricardo Reis transformations in its re-reading aspects, as a narrative formed by other texts and references, primarily Pessoa, but also other literary works, especially Camões and Borges, and history itself, which constitutes the spectacle with which the heteronym-character is confronted in the narrative. The reading and the opening of the text appear thus as a point of departure and arrival in the reflection about the multiple labyrinths that form the novel, from literature to history, from Pessoa to the dra-matic interwar period in which Ricardo Reis is set